Nuclear design of 400 MW pool-type low-temperature heating reactor core - HU Binhe; LIU Xingmin; SUN Zheng; KE Guotu (He jishu, 2021)
BackgroundAs a kind of clean energy, nuclear energy has obvious advantages in reducing fossil energy consumption and pollutant emission. Nuclear energy can be used to provide not only electric energy, but also direct heating.PurposeThis study aims to design and optimize the pool type heating reactor core to make it with good economy and safety.MethodsThe core of heating reactor was located in the deep pool to make use of static pressure of the deep water for the outlet temperature elevating to meet the requirements of the heating system. The nuclear design of a core with 69 assemblies was applied to 400 MW pool-type heating reactor, it was characterized by truncated pressurized water reactor (PWR) assemblies, low power density, long cycle length, non-boron reactivity control mechanism. The gadolinium fuel rods was used to provide a part of backup reactivity. The burn-up of each cycle was calculated, and the important physical parameters were analyzed. Finally, the core design criteria were given, the loading mode of the core and the rod withdraw sequence were optimized.ResultsCalculation results show that the maximum discharge burnup is 31.10 GW·d·t-1 (U). The shutdown depth of the first and second shutdown system are 0.065 69 and 0.029 71, respectively.ConclusionsRelevant research and calculation in this study demonstrate that the core with 69 assemblies meets the relevant nuclear design criteria and has good economy and safety.